Structural promiscuity in the human circulatory IgA1 clonal repertoire - Amber D. Rolland; Sofia Kalaidopoulou Nteak; Gestur Vidarsson; Albert Bondt; Albert J. R. Heck (Proceedings of the National Academy of Sciences, 2026)
Immunoglobulin A (IgA) is the most abundant antibody in humans, with high concentrations in both mucosae/secretions and circulation. While mucosal IgA has been studied extensively, characterization of human IgA in serum and its distinctive functions lags behind. Circulatory IgA is regularly assumed to be monomeric, despite some reports describing a minor population of J-chain-coupled dimers. Here, we first charted the compositional landscape of human serum IgA in individual healthy donors. In addition to the expected predominating monomers, we consistently observed J-coupled dimers, even representing ~30% of one donor’s total serum IgA. To determine whether these structurally distinct populations were also clonally distinct, we employed mass spectrometry–based IgA1 clonal profiling in sera of two donors. Our data revealed the majority of IgA1 clones are present solely as monomers, with a smaller number exclusively dimeric. Strikingly, a third population of IgA1 clones is present in circulation as both monomers and J-coupled dimers. In fact, these shared, structurally promiscuous IgA1 clones dominated both individuals’ serum IgA1 clonal repertoires. Our findings suggest every unique IgA1 clone could potentially be produced as a variable mixture of monomers and J-coupled dimers, but what exactly determines this ratio requires further investigation. This finding is important, as monomers and J-coupled dimers have distinct characteristics in antigen binding, receptor activation, and clearance from circulation, with several reports highlighting, for instance, the enhanced neutralization capacity of dimeric IgA. As we show here, the human immune system is not merely capable of producing both forms but apparently prefers doing so in parallel.